2015
DOI: 10.3109/02699052.2015.1035325
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient follow-up and return to school after emergency department evaluation among children with persistent post-concussion symptoms

Abstract: Objective To describe differences in outpatient follow-up and academic accommodations received by children with and without persistent post-concussion symptoms (PPCS) after emergency department (ED) evaluation. We hypothesised that children with PPCS would have more outpatient visits and receive academic accommodations more often than children without PPCS and that follow-up would be positively associated with receiving accommodations. Methods Children aged 8–18 years with acute (≤6 hours) concussion at time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…As expected, there was a gradual and steady reduction of PCS over the first 3 weeks across both cognitive and somatic functioning. In line with findings from prior research (7,40), we found that 20% reported PCS at 3 weeks after concussion, and 12% of adolescents continued to experience PCS at 3 months after injury. We also examined trajectories of sleep deficiency (i.e., increased daytime sleepiness, reduced sleep duration, increased insomnia symptoms) finding variability over time.…”
Section: Discussionsupporting
confidence: 91%
“…As expected, there was a gradual and steady reduction of PCS over the first 3 weeks across both cognitive and somatic functioning. In line with findings from prior research (7,40), we found that 20% reported PCS at 3 weeks after concussion, and 12% of adolescents continued to experience PCS at 3 months after injury. We also examined trajectories of sleep deficiency (i.e., increased daytime sleepiness, reduced sleep duration, increased insomnia symptoms) finding variability over time.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, 44.7% of patients had worsening symptoms when they prematurely progressed through a return-to-learn protocol. Similarly, Grubenhoff et al 22 observed that adolescents with persistent postconcussive symptoms (ie, .1 month) missed 50% more school days than adolescents without such symptoms. However, the percentage of patients who received academic adjustments did not differ between those with and those without postconcussive symptoms, suggesting underuse of academic adjustments for patients who would likely benefit.…”
Section: Use Of Restmentioning
confidence: 88%
“…The ability to identify factors associated with longer symptom duration soon after injury can help to guide clinicians making decisions about initiating therapy, assist with anticipatory guidance, and help patients prepare for difficulties at work and school caused by their symptoms . Factors such as loss of consciousness at the time of injury , amnesia at the time of injury , post‐traumatic migraine , anthropometric characteristics or previous concussion history have been identified as risk factors for developing persistent postconcussion symptoms in prior studies.…”
Section: Introductionmentioning
confidence: 99%